Relationship between Nurses' Work Motivation and Nurses' Interprofessional Collaboration Practice toward Patient Satisfaction - Hezlin Ivana Miryam Marbun; Siti Saidah Nasution; Rika Endah Nurhidayah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Nurse work motivation is the internal and external forces that drive work behaviors, such as commitment and performance, by determining their direction, intensity, and duration. Interprofessional collaboration in nursing practice involves partnerships between nurses, healthcare teams, and patients with shared decision-making based on professional expertise. Patient satisfaction reflects perceptions of the quality of care compared to their expectations. This study aims to analyze the relationship between nurses' work motivation and patient satisfaction and the relationship between interprofessional collaboration in nursing practice. The study was quantitative with a correlation approach. 99 inpatients were involved in this study using convenience sampling. Data were collected using a questionnaire and analyzed using the Spearman rank statistical test. The results of the study showed that there was a relationship between nurse work motivation and patient satisfaction (0.027<0.05). There was a relationship between nurse interprofessional collaboration practice and patient satisfaction 0.007<0.05). It is expected that the work motivation and interprofessional collaboration practice of nurses can be further improved in services so that patient satisfaction increases and patient needs are met well.